An Association Study on the Cognitive Function and the Cerebral Grey Matter Volume of Patients with First-Episode Schizophrenia. Issue 3 (25th July 2018) - Zhang, Xinyue; Yao, Jingjing; Lv, Yiding; Zhao, Xiaoxin; Li, Yuan; Sui, Yuxiu; Dai, Zhiping
Abstract : Background: The impairment of cognitive function is one of the core symptoms in schizophrenia, and the degree of recovery is closely related to whether patients are able to rejoin society successfully. Objective: This study was to clarify the correlation between cognitive function and cerebral grey matter volume in schizophrenia. Methods: The neuro-cognitive functions of thirty-seven patients with first-episode schizophrenia (the patient group) and thirty healthy controls (the control group) was evaluated with the Clock Drawing Test, Trail Marking Test, Digit Span Test, Auditory Verbal Learning Test, Wisconsin Card Sorting Test, Verbal Fluency Test, Semantic Similarity Test and Stroop Color-Word Test. The facial emotion cognitive task was employed to assess the facial emotion cognitive functions of thirty-two patients with first-episode schizophrenia (the patient group) and 29 healthy controls (the control group). The psychotic symptoms of patients with first episode schizophrenia were evaluated using the Positive and Negative Syndrome Scale (PANSS). The brain imaging data of the patient group and control group were collected using the magnetic resonance imagine (MRI). Results: The difference between the patient group and the control group in the results of Clock Drawing Test, Trail Marking Test, Digit Span Test, Auditory Verbal Learning Test, Wisconsin Card Sorting Test, Verbal Fluency Test, Semantic Similarity Test and Stroop Color-Word Test's reaction time were significant. These two groups' Slopes in the facial emotion cognitive task were also significantly different from each other. According to the comparison of cerebral grey matter volume between the patient group and the control group, it was found that the grey matter volume of the patient group increased in the left superior frontal gyrus, and decreased in the left occipital gyrus, lingual gyrus and upper cerebellum. Based on the analyses of neuro-cognitive data and brain imaging data of the patient group, the scores of the number of correct responses in Stroop Color-Word Test's Card C were negatively correlated with grey matter volumes of the left upper frontal gyrus, right upper frontal gyrus and middle frontal gyrus. The analyses on the facial emotion cognitive task and brain imaging data of the patient group showed that the slope data were positively correlated with grey matter volumes of the right superior temporal gyrus, middle temporal gyrus, left middle temporal gyrus, inferior temporal gyrus and fusiform gyrus. Conclusion: There are general impairments in the neuro-cognitive functions and facial emotion cognitive functions of patients with first-episode schizophrenia, and the results suggest that brain areas with abnormal grey matter volumes are likely to be the brain structure and functional basis of the cognitive impairments.